LEAF MORPHO-ANATHOMICAL CHARACTERISTICS OF FIVE POTATO CLONES - Bisognin, Dilson Antônio; Segatto, Fernanda Bastos; Manfron, Paulo Augusto; Muller, Douglas Renato; Rampelotto, Marcos Vicente (Ciência e Natura, 2006)
Host genetic resistance against pathogens and insects can bedirectly associated with leaf morpho-anathomical characteristics. The aimwas to study leaf morph-anatomical characteristics of five potato (Solanumspp.) clones differing in ploidy level and genetic background. The epidermisand mesophyll were characterized and stomata and trichome frequenciesdetermined in both adaxial and abaxial surfaces of plant main leaflets. Therewere no evident differences in cuticle thickness and epidermis compositionamong evaluated clones. Clones of S. microdontum Bitter and SMII had apalisade parenchyma with uniform, long and compact arranged cellscompared to other clones. There were no morphological differencesbetween stomata subsidiary and other epidermal cells. The S. microdontumclone showed the highest frequency of stomata, on the abaxial surface, andtrichomes, on both leaflet surfaces. Differences in stomata and trichomefrequencies among clones need to be accessed to find possible relationshipwith disease and/or pest resistance.Key words: Solanum tuberosum, foliar anatomy, stomata and trichomefrequencies, resistance breeding.